Fast Fault Recovery Technique for Monopolar HVDC Systems Based on New Control Strategy. Issue 11 (21st July 2018) - Dehghan Marvasti, Farzad; Mirzaei, Ahmad
Abstract: This paper presents a new fast control strategy method for enhancing the fault-ride-through performance of monopolar high voltage direct current systems in case of a DC line fault. The proposed method is solely based on a novel control strategy algorithm, which will be functional after detecting the DC internal faults. The new control method is able to prevent the DC voltage from becoming negative during the force alpha period and is also able to exceed the recovery speed of the system by switching the controlling method from current controller to gamma controller during the recovery process. These two facts are the main ideas behind the new control strategy that will improve the recovery process of the system by a great margin. To evaluate the reliability of the proposed method, the Hydro-Quebec monopolar high voltage direct current test system using MATLAB/SIMULINK environment is used. It will be shown that the proposed method is not only functional for recovering the system in case of any DC fault occurrence but also more economical and well applicable on the existing high voltage direct current networks.